Prevalence of Helicobacter pylori as coinfection in Iraqi patients infected with viral hepatitis types (World Journal of Experimental Biosciences, 2016)
Helicobacter pylori is slightly responsible for liver diseases in many countries, prevalence of H. pylori as co-infection in Iraqi patients with viral hepatitis types problem is scanty in literature. Here, 63 Iraqi patients infected with viral hepatitis types HAV, HBV, HCV and HEV diagnosed by sera examination were recognized with bioelasia kit, and 30 healthy persons as a control were studied. The patients and healthy persons screened for H. pylori infection by examine anti- H. pylori in their sera. The result of diagnostic tests was analyzed statistically by percentage ratio, chi-square test, relative risk ratio and odds ratio. The results of showed that the relative risk of a viral hepatitis patients getting H. pylori was 74.6% about four times higher than risk of control getting H. pylori (16.7%), each of chi-square test, relative risk ratio and odds ratio showed significant differences values. The percentage of positive H. pylori in viral hepatitis types A, B, C and E types were 7.9%, 47.6%, 15.9% and 6.34%, respectively. The study demonstrated high prevalence of H. pylori in patients with HBV compared with patients infected with other types of hepatitis. Also the study manifested high percentage in male with coinfection of H. pylori compare with female, while the percentage of positive infected of H. pylori in viral hepatitis types depending on gender and type of hepatitis virus. In the HBV the highest percentage in male and female 39.7% and 22.2% respectively and in the HEV was the lowest percentage in male and female 4.8% and 6.3%, respectively.